How Mendeley Software Enhances Students' Scientific Writing through Mentorship and Training Opportunities - Kusumaningsih, Dewi; Darmayanti, Rani; Latipun, Latipun (CV. BImbingan Belajar Assyfa, 2024)
Accredited and global journals increasingly emphasize the necessity of Mendeley-based article writing. Many authors still rely on manual citation and bibliography creation, which is time-consuming and prone to errors. This study addresses the challenges faced by students in managing bibliographies and avoiding plagiarism due to the manual process. By leveraging Mendeley's automatic bibliography generation, students can significantly improve the quality and efficiency of their scientific writing. This community service activity involved a combination of lectures, discussions, and technical guidance (BIMTEK) to enhance students' understanding and skills in using Mendeley. The results showed a marked improvement in participants' ability to install and utilize the software effectively. Detailed analysis of the training process and outcomes will be discussed to provide insights into best practices for mentorship and training in scientific writing.